Value assessment of antimicrobials and the implications for development, access, and funding of effective treatments: Australian stakeholder perspective. (3rd November 2020) - Hillock, Nadine T.; Merlin, Tracy L.; Karnon, Jonathan; Turnidge, John; Eliott, Jaklin
Abstract: Background: The frameworks used by Health Technology Assessment (HTA) agencies for value assessment of medicines aim to optimize healthcare resource allocation. However, they may not be effective at capturing the value of antimicrobial drugs. Objectives: To analyze stakeholder perceptions regarding how antimicrobials are assessed for value for reimbursement purposes and how the Australian HTA framework accommodates the unique attributes of antimicrobials in cost-effectiveness evaluation. Methods: Eighteen individuals representing the pharmaceutical industry or policy-makers were interviewed. Interviews were transcribed verbatim, coded, and thematically analyzed. Results: Key emergent themes were that reimbursement decision-making should consider the antibiotic spectrum when assessing value, risk of shortages, the impact of procurement processes on low-priced comparators, and the need for methodological transparency when antimicrobials are incorporated into the economic evaluation of other treatments. Conclusions: Participants agreed that the current HTA framework for antimicrobial value assessment is inadequate to properly inform funding decisions, as the contemporary definition of cost-effectiveness fails to explicitly incorporate the risk of future resistance. Policy-makers were uncertain about how to incorporate future resistance into economic evaluations without a systematic method to capture costs avoided due to good stewardship. Lacking financial reward for the benefits of narrower-spectrum antimicrobials, companies will likely focus on developing broad-spectrum agents with wider potential use. The perceived risks of shortages have influenced the funding of generic antimicrobials in Australia, with policy-makers suggesting a willingness to pay more for assured supply. Although antibiotics often underpin the effectiveness of other medicines, it is unclear how this is incorporated into economic models.